Shenkang injection improves chronic kidney disease by inhibiting multiple renin-angiotensin system genes by blocking the Wnt/β-catenin signalling pathway - Wang, Yan-Ni; Liu, Hong-Jiao; Ren, Li-Li; Suo, Ping; Zou, Liang; Zhang, Ya-Mei; Yu, Xiao-Yong; Zhao, Ying-Yong (Frontiers in Pharmacology, 2022)
Chronic kidney disease (CKD) is a major worldwide public health problem. The increase in the number of patients with CKD and end-stage kidney disease requesting renal dialysis or transplantation will progress to epidemic proportions in the next several decades. Although blocking the renin-angiotensin system (RAS) has been used as a first-line standard therapy in patients with hypertension and CKD, patients still progress towards end-stage kidney disease, which might be closely associated with compensatory renin expression subsequent to RAS blockade through a homeostatic mechanism. The Wnt/β-catenin signalling pathway is the master upstream regulator that controls multiple intrarenal RAS genes. As Wnt/β-catenin regulates multiple RAS genes, we inferred that this pathway might also be implicated in blood pressure control. Therefore, discovering new medications to synchronously target multiple RAS genes is necessary and essential for the effective treatment of patients with CKD. We hypothesized that Shenkang injection (SKI), which is widely used to treat CKD patients, might ameliorate CKD by inhibiting the activation of multiple RAS genes via the Wnt/β-catenin signalling pathway. To test this hypothesis, we used adenine-induced CKD rats and angiotensin II (AngII)-induced HK-2 and NRK-49F cells. Treatment with SKI inhibited renal function decline, hypertension and renal fibrosis. Mechanistically, SKI abrogated the increased protein expression of multiple RAS elements, including angiotensin-converting enzyme and angiotensin II type 1 receptor, as well as Wnt1, β-catenin and downstream target genes, including Snail1, Twist, matrix metalloproteinase-7, plasminogen activator inhibitor-1 and fibroblast-specific protein 1, in adenine-induced rats, which was verified in AngII-induced HK-2 and NRK-49F cells. Similarly, our results further indicated that treatment with rhein isolated from SKI attenuated renal function decline and epithelial-to-mesenchymal transition and repressed RAS activation and the hyperactive Wnt/β-catenin signalling pathway in both adenine-induced rats and AngII-induced HK-2 and NRK-49F cells. This study first revealed that SKI repressed epithelial-to-mesenchymal transition by synchronously targeting multiple RAS elements by blocking the hyperactive Wnt/β-catenin signalling pathway.